Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1177/2051415817689977
|View full text |Cite
|
Sign up to set email alerts
|

Can an operative coding sticker improve coding accuracy and remuneration for upper tract stone-related procedures?

Abstract: Objective: Rigid ureteroscopy, flexible uretero-renoscopy and ureteric stenting are commonly performed procedures. Operative clinical coding and remuneration varies depending on the procedure. We determined if loss of remuneration, through poor operative coding, could be improved with an operative coding sticker. Patients and methods: We performed a retrospective review of 133 random stone-related procedures (rigid ureteroscopy/flexible uretero-renoscopy and ureteric stenting). Using the Office of Population C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Reported data relate to finished consultant episodes (FCEs). Using the OPCS-4 procedural codes, we were able to identify all stone-related procedures [6][7][8][9][10] . Data collected included the following: age, demographics, location and nature of the procedures, emergency workload, length of stay (LoS) and procedural day-case rates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported data relate to finished consultant episodes (FCEs). Using the OPCS-4 procedural codes, we were able to identify all stone-related procedures [6][7][8][9][10] . Data collected included the following: age, demographics, location and nature of the procedures, emergency workload, length of stay (LoS) and procedural day-case rates.…”
Section: Methodsmentioning
confidence: 99%
“…In the past, criticism has been leveled at HES data in terms of its accuracy as it relies largely upon coding data, recorded from patient notes, by non-clinicians in NHS hospitals, at the time of patient discharge [5] . Furthermore, a recent paper that investigated the accuracy of clinical coding for upper tract URS found that up to 55% of the coding data can be erroneous, with the particular error of renal URS being coded as ureteric URS [6] . In spite of this, a recent systematic review demonstrated a median accuracy of 84.2% for recorded procedure data within the HES database [7] .…”
Section: Strengths Of Our Studymentioning
confidence: 99%
“…We have previously shown that ureteroscopy (URS) has been miscoded in over 50% of cases, mainly due to a lack of understanding from the coders about the procedure undertaken. 8 We previously introduced a URS coding sticker, and evaluated its role in coding accuracy and remuneration for URS.…”
Section: Discussionmentioning
confidence: 99%
“…4 Studies in urology and other surgical specialties have demonstrated considerable variation in coding accuracy with inevitable financial implications. [5][6][7][8] Reviews of coding errors have deemed these as multi-factorial in origin; however, a major determinant relates to clinical interpretation of notes. 9 To improve the accuracy of clinical coding in our hospital, an operative coding sticker for PCNL was designed which listed all potential components of PCNL ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%